CRUDE PROTEIN CONTENT, CRUDE FAT AND CRUDE FIBER FERMENTED CASSAVA TUBER PEEL (KUUK) WITH ECO ENZYMES - Risdawati Br Ginting; Dini Julia Sari Siregar; Warisman Warisman; Ryan Renanda Putra (Journal of Innovation Research and Knowledge, 2023)
This study aims to determine the nutrition of cassava tuber skin (KUUK) fermented with eco enzyme. The method used in this study was using a Factorial Complete Randomized Design (RAL), which consisted of 3 treatments, namely P0 = Cassava tuber skin without fermentation; P1= Fermentation of eco enzyme 10 ml; P2 = Fermentation of eco enzyme 20 ml, and repeated as many as 5 repeats. The observed modifiers were changes in crude protein content, crude fiber, and crude fat. The results showed that fermentation of cassava tuber peel (KUUK) had a very noticeable effect (P< 0.05) on crude protein, crude fiber and crude fat. The conclusion of this study is that the best nutritional content is obtained in E2 treatment (fermented eco enzyme 20 ml) with crude fiber nutrient content of 6.960%, crude protein 7.538%, and crude fat 0.321%.